The People’s Dictator - Quiroga, Alejandro (Taylor & Francis, 2025)
This book is the first major biography of General Miguel Primo de Rivera, dictator of Spain between 1923 and 1930, who played a key role in the shaping of a counterrevolutionary Europe in the interwar era.